The Islamic Studies and the Study of Religions by the Early Indonesian Muslim Scholars - Alfina Hidayah; Hamdan Maghribi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This research is an effort to raise the development of religious studies (Islamic Studies) and the study of religions that already emerged and developed in the archipelago before twentieth century. This can be known through the figures of previous Muslim scholars and their works on these topics. The research process uses qualitative methods on a literature review which will be delivered descriptively. While the aim of research is to find out how the Muslim scholars of Indonesian Archipelago have contributed in various aspects particularly in the field of knowledge and intellectual supported by their extraordinary works in the form of books, poem, etc. As a manifestation of their role in da'wah in addition to enrich the scientific treasures. So it can be concluded in a broad outline that additionally to the Nine Saints (Wali Sanga), the archipelago has Muslim scholars who have taken part in Islamic preaching and furthermore they explored their teachings into wonderful works, both on Islamic (religious) studies as well as the study of religions.Keywords: Islamic Studies, Study of Religions, Indonesian Muslim Scholar AbstrakPenelitian ini adalah upaya untuk mengangkat tentang perkembangan kajian keagamaan (Islam) maupun studi tentang agama-agama yang telah lama muncul dan berkembang di Nusantara sebelum abad 20. Hal tersebut dapat diketahui melalui tokoh-tokoh ulama muslim terdahulu beserta karya-karya mereka yang mengkaji tema-tema tersebut. Proses penelitian ini menggunakan metode kualitatif dan juga merupakan kajian pustaka yang akan disampaikan secara deskriptif. Adapun tujuan penelitian untuk mengetahui bagaimana ulama muslim Nusantara telah berkontribusi dalam berbagai aspek dan salah satu nya adalah secara intelektual mereka melahirkan karya-karya luar biasa baik berupa buku, puisi, dsb sebagai wujud dari peran dakwah sekaligus memperkaya khazanah keilmuan. Sehingga dapat disimpulkan secara garis besar bahwa selain para Wali Sembilan (Wali Sanga), Nusantara memiliki ulama-ulama muslim yang telah banyak berkiprah dalam berdakwah serta menuliskan pokok-pokok ajarannya dalam karya-karya mereka, baik tentang kajian keislaman juga kajian agama-agama.Kata Kunci: Kajian Islam, Kajian Agama-Agama, Ulama Muslim Nusantara